Artesunate-tinospora combination treatment decreases nuclear factor kappa-B and intercellular adhesion molecule-1 expression in mouse malarial models - Izzati, Nur; Fitri, Loeki Enggar; Dalhar, Mochammad (Faculty of Medicine, Trisakti University, 2016)
BackgroundCerebral malaria is a severe form of malaria caused by brain ischemia. Artesunate, an artemisinin derivative, is the standard WHO therapy for severe malaria. Tinospora crispa (brotowali) is a traditional plant with antiinflammatory, antioxidant and antiparasitic properties. The aim of this study was to determine the effect of combinations of artesunate and T. crispa extract on nuclear factor kappa-B (NFêB) and intercellular adhesion molecule-1 (ICAM-1) expression in the brain of mouse malaria models.MethodsThis was an experimental post-test only control group study using C57BL/6J mice infected with Plasmodium berghei, divided into 7 groups: negative control, positive control, group receiving artesunate 32 mg/kgBW, group receiving tinospora extract 3.5 mg/kgBW, and three groups receiving combinations of artesunate 32 mg/kgBW and tinospora extract 2.5 mg/kgBW, 3 mg/kgBW and 3.5 mg/BW, respectively. The expression of NFêB and ICAM-1 was measured by immunohistochemistry. One-way ANOVA was used to analyze the data.ResultsNFkB and ICAM-1 expression increased significantly in the positive controls compared to all other groups (p=0.000). NFkB expression was significantly lower in the groups receiving artesunate and tinospora at 3 mg/kgBW and 3.5 mg/kgBW, as compared with the artesunate only group (p=0.003; p=0.005) and the tinospora extract only group (p=0.001; p=0.003). NFkB expression in all combination treatment groups was similar to that in the negative controls (p>0.05), whereas ICAM-1 expression did not differ between single and combination treatment groups (p>0.05). ConclusionThe combination of artesunate and T. crispa extract is better in decreasing NFêB and ICAM-1 expression in the brain of mouse malaria models.